Dampak Perubahan Iklim dan Paparan Bencana terhadap Ketahanan Pangan di Provinsi Banten, Indonesia (2018-2023) - Rahmat, Jalaludin; Budiawati, Yeni; Sulaeni, Sulaeni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study investigates how climate change and disaster exposure influence food security in Banten Province, Indonesia, over the period 2018–2023. Using a panel data regression approach with the Random Effects Model, the analysis incorporates key indicators of climate variability—including temperature and rainfall changes—as well as disaster-related factors such as the number of affected facilities, affected individuals, and disaster frequency. The findings indicate that variations in rainfall and infrastructure-related disaster impacts significantly affect food security outcomes, suggesting a critical link between environmental stressors and food system resilience. These results contribute to the growing body of evidence on regional food security vulnerabilities in the context of climate and disaster risks, and provide policy-relevant insights for enhancing local adaptation strategies.